AKUNTABILITAS LAPORAN KEUANGAN KOPERASI (Studi pada Koperasi Osseda Faolala Perempuan Nias) - Anskaria Simfrosa Gohae (LPPM Universitas Nias Raya, 2022)
This research aims to find out how accountability or accountability of the financial statements of the Osseda Faolala Perempuan Nias Cooperative Unit Luahagundre Maniamolo Subdistrict. OFPN Cooperative Accountability is reviewed from the preparation of cooperative financial statements. The results of the research review concluded that it had not been optimal preparation of financial statements by SAK ETAP according to indications of the preparation of reports, both monthly reports (loans or receivables and customer deposits) or annual. It is expected that in the future that the Osseda Faolala Perempuan Nias Cooperative (KOFPN) can compile financial statements by the ETAP SAK that has been established so that member trust can be increased and more accountability is maintained.